2016
DOI: 10.1016/j.jfda.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of herbal mixture extracts on obesity in rats fed a high-fat diet

Abstract: The aim of this study was to investigate and compare the effects of three herbal mixture extracts on obesity induced by high-fat diet (HFD) in rats. The prescriptions-Pericarpium citri reticulatae and Fructus crataegi-were used as matrix components and mixed with Ampelopsis grossedentata, Salvia miltiorrhiza, and epigallocatechin-3-gallate (EGCG) to form T1, T2, and T3 complexes, respectively. Results revealed that HFD feeding significantly increased body weight gain, fat deposition, plasma lipid profiles, hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 31 publications
1
39
0
4
Order By: Relevance
“…Meli et al [41] established that HFD induced hepatic steatosis in mice and rats. In addition, Chien et al [42] reported that HFD feeding significantly increased liver weight, hepatic triglycerides and total cholesterol accumulation and hepatic vacuoles.…”
Section: Discussionmentioning
confidence: 99%
“…Meli et al [41] established that HFD induced hepatic steatosis in mice and rats. In addition, Chien et al [42] reported that HFD feeding significantly increased liver weight, hepatic triglycerides and total cholesterol accumulation and hepatic vacuoles.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini sesuai dengan penelitian yang dilakukan Nikasa et al (2016) yang menunjukkan bahwa diet tinggi kolesterol secara signifikan meningkatkan bobot badan tikus. Beberapa penelitian serupa menunjukkan bahwa tikus yang diberikan pakan tinggi lemak bobot badannya akan meningkat secara signifikan (Davidson et al 2010;Chien et al 2016;Marques et al 2016). Pada minggu ketiga dan keempat mulai diberikan intervensi berdasarkan kelompok perlakuan.…”
Section: Perubahan Bobot Tikusunclassified
“…Srimiati et al (2015) mengatakan bahwa minyak ikan lele mengandung omega 6 dan omega 3 walaupun perbandingan omega 6 lebih tinggi dari omega 3. Hal ini sesuai dengan pernyataan Chen et al (2016) yang menyatakan bahwa pemberian omega 3 dapat meningkatkan steatosis hati dan memperbaiki fungsi hati.…”
Section: Perubahan Histopatologi Hatiunclassified
“…Higher serum AST, ALT, and free fatty acids, as well as liver TC, TG, TBARS, and cytokine levels were easily observed in a HFD fed rodent models [22,27,28]. It has been reported that the hepatoprotection of OSM against CCl 4 resulted in decreased serum AST and ALT values.…”
Section: Discussionmentioning
confidence: 97%